Sustainable agricultural practices and their impact on ecological indicators: A case study of cherry production in Iran - Fatemeh Meftahi; Amir Azizpanah; Morteza Taki (Sustainable Futures)
Global environmental crises and resource depletion have severely impacted food security worldwide, necessitating a shift toward sustainable agricultural practices that balance productivity with environmental conservation. While numerous studies have evaluated energy use and Greenhouse Gas (GHG) emissions in major field crops, there remains a significant research gap in the context-specific analysis of fruit crops—particularly cherry production—where energy dynamics, emission profiles and economic viability are less understood, especially in semi-arid regions like Iran. This study addresses this gap by optimizing the Global Warming Potential (GWP) and energy sustainability for cherry production in Lavasan city, Tehran province, Iran. Data were collected from 30 cherry farmers through structured questionnaires and face-to-face interviews. Energy use, GHG emissions, economic performance and sustainability indices were calculated and evaluated. Data Envelopment Analysis (DEA) under Constant Return to Scale (CRS) and Variable Return to Scale (VRS) models identified 16 and 17 efficient units, respectively. After optimization, total energy consumption decreased to 4,463.05 MJ ha-1, energy ratio improved from 1.7 to 2.1, and pure energy gain increased from 19,782.27 to 24,245.31 MJ ha-1. Diesel fuel and human labor consumption were reduced by 16.2% and 11.3%, respectively. GWP decreased significantly from 1,246.14 to 682.45 kg CO₂ ha-1, while carbon efficiency improved from 20.52 to 31.96. The sustainability index rose from 19.52 to 30.96. Economic analysis revealed a production cost of $5,580.58 ha⁻¹ and a gross product value of $26,948.06 ha-1, yielding a profit-cost ratio of 0.86.